Sistem Informasi Pengajuan Layanan Administrasi Kependudukan Dari Desa Dan Kelurahan ke Dinas Kependudukan Dan Pencatatan Sipil Berbasis Web. - Warda Wulandari; Shinta Esabella; Farida Idifitriani; Yunanri (Buletin Ilmiah Informatika Teknologi, 2023)
Information System for Submitting Population Administration Services from Villages and Sub-districts to the Department of Population and Civil Registration based on Web Technology" conducted at the Department of Population and Civil Registration in Sumbawa. The purpose of this research is to design and develop an Information System for Submitting Administrative Services that can facilitate village officers in the production of population documents. The background of this research is the implementation of service innovation presented by the Department of Population and Civil Registration of Sumbawa Regency, which still uses email for administrative services, causing confusion among the public due to the lack of service requirements. In this research, the Rapid Application Development method is used. The application is web-based and built using PHP programming language, MySQL database, and a framework. System planning is carried out using structured design by defining context diagrams, DFD, and ERD, and it is tested using blackbox testing. The Information System for Submitting Population Administration Services can facilitate the public, through villages and sub-districts, in managing administrative service requests. It also serves as a data and information storage medium for population records for those who apply for administrative services. This research successfully builds an information system for submitting administrative services, which demonstrates that the system can correctly display notification information regarding requirements and submission data, and it serves as a prototype to provide input to the Department of Population and Civil Registration of Sumbawa Regency to develop and assist villages in connecting with the Department to provide information on population administration service requirements to the public, especially village officers, in the process of creating population documents.